2005
DOI: 10.1103/physrevb.71.024431
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Mössbauer study of spin-glass behavior inFeAl2

Abstract: We have used NMR and Mössbauer spectroscopy to investigate the magnetism and spin-glass behavior in FeAl 2 . The results show that the observed behavior can be interpreted as local-moment magnetism residing on the Fe sites. An increase in 57 Fe Mössbauer magnetic hyperfine field was observed at the 35-K spin-glass freezing temperature, with a reduced low-temperature value consistent with unquenched fluctuations in the spin-glass state. However, the 27 Al NMR shifts and spin-lattice relaxation behavior are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…1,2 Experimental and theoretical evidences have established that this anomaly corresponds to a pure SG freezing transition, [4][5][6] which takes place at temperatures near 30 K. For ordered Fe 0.7 Al 0.3 single crystals, this transition was reported to be of the re-entrant spin-glass ͑RSG͒ type with a freezing temperature of ϳ80 K. 7,8 The second phenomenon is the superparamagneticlike ͑SP͒ behavior initially proposed by Cable et al 10 for alloys with a composition around 30 at. % Al.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Experimental and theoretical evidences have established that this anomaly corresponds to a pure SG freezing transition, [4][5][6] which takes place at temperatures near 30 K. For ordered Fe 0.7 Al 0.3 single crystals, this transition was reported to be of the re-entrant spin-glass ͑RSG͒ type with a freezing temperature of ϳ80 K. 7,8 The second phenomenon is the superparamagneticlike ͑SP͒ behavior initially proposed by Cable et al 10 for alloys with a composition around 30 at. % Al.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical alloying being a high energy, non-equilibrium process, in addition to producing a high degree of chemical disorder, also introduces defects and strain. These effects result in a larger degree of distortion at 57 Fe sites leading to a larger quadrupole splitting in comparison to the value in an ordered alloy as used by Chi et al [36]. As pointed out earlier, the magnetic hyperfine sextet of the Mössbauer spectra of the as milled samples (Fig.…”
Section: Mössbauer Studiesmentioning
confidence: 81%
“…The magnetism in the nonmagnetic ordered Fe-Al alloy (B2 structure) was induced by the ball milling because of the iron atom clustering on the grain boundaries [9]. Furthermore, a similar low temperature magnetism of Al-rich Fe-Al alloys was also observed for the FeAl 2 intermetallic compound having a more complicated Fe-Al atom ordering where iron atoms have a different number of iron atoms in their neighbourhood [15,16]. Theoretical calculations of the ground state of (FeAl) n (n≤6) clusters revealed that iron atoms cluster due to the domination of Fe-Fe atom interactions [17].…”
Section: Introductionmentioning
confidence: 89%